Implementasi Interpetasi Standar Akuntansi Keuangan (ISAK 35) Pada Sektor Pendidikan (Studi Kasus Pada Unit Pelaksana Teknis Sekolah Menengah Pertama Negeri 32 Gresik) - Alvin Prasetya Adji; Maulidah Narastri (FEB Universitas Maritim Semarang, 2023)
This study aims to apply the concepts of ISAK 35 to the field of education. This study aims to determine the implementation of school financial management from the prespective of ISAK 35. This study also uses descriptively presented qualitative data types, uses primary and secondary data sourses, and uses data collection techniques in the form of interview and concluded that SMPN 32 Gresik’s management and financial records remained rudimentary, limited to recording school financial income and expenditure, and did not comply with ISAK 35 financila reporting.